2014
DOI: 10.1016/s0325-7541(14)70094-x
|View full text |Cite
|
Sign up to set email alerts
|

Response of ligninolytic macrofungi to the herbicide atrazine: dose-response bioassays

Abstract: The effect of atrazine concentrations on mycelial growth and ligninolytic enzyme activities of eight native ligninolytic macrofungi isolated in Veracruz, México, were evaluated in a semi-solid culture medium. Inhibition of mycelial growth and growth rates were significantly affected (p=0.05) by atrazine concentrations (468, 937, 1875, and 3750 mg/l). In accordance with the median effective concentration (EC50), Pleurotus sp. strain 1 proved to be the most tolerant isolate to atrazine (EC50=2281.0 mg/l), althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…However, on the other extreme, atrazine was the least potent of the herbicides to the point that it completely failed to arrest the mycelial growth of T. viride even at the highest concentration tested. This corroborate the findings of Rodriguez-Kahana et al [14], who had earlier reported that all the concentrations of atrazine tested, 8, 20, 40 and 80 ppm enhanced T. viride growth; and that of Cupul et al [13], who reported that although, atrazine inhibited the mycelial growth rate of all the tested macrofungi (Cymatadoderma elegans, Daedalea elegans, Pleurotus djamor, Pleurotus sp., Pycnoporus sanguineus and Trametes maxima), non reached 100% under the tested doses(468, 937, 1875 and 3750 mgL -1 )with some fungi not inhibited at all at lower doses, and concluded that moderate doses of atrazine are not toxicto the fungi. Variation in the degree of mycelial growth inhibition may be attributed to the differential toxicity of the herbicides arising from their chemical composition and the degradative capacity of the respective fungi.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, on the other extreme, atrazine was the least potent of the herbicides to the point that it completely failed to arrest the mycelial growth of T. viride even at the highest concentration tested. This corroborate the findings of Rodriguez-Kahana et al [14], who had earlier reported that all the concentrations of atrazine tested, 8, 20, 40 and 80 ppm enhanced T. viride growth; and that of Cupul et al [13], who reported that although, atrazine inhibited the mycelial growth rate of all the tested macrofungi (Cymatadoderma elegans, Daedalea elegans, Pleurotus djamor, Pleurotus sp., Pycnoporus sanguineus and Trametes maxima), non reached 100% under the tested doses(468, 937, 1875 and 3750 mgL -1 )with some fungi not inhibited at all at lower doses, and concluded that moderate doses of atrazine are not toxicto the fungi. Variation in the degree of mycelial growth inhibition may be attributed to the differential toxicity of the herbicides arising from their chemical composition and the degradative capacity of the respective fungi.…”
Section: Discussionsupporting
confidence: 90%
“…To understand fungal capacity to colonize and settle on a particular substrate, it is important to study their growth rate [13]. Of all the herbicides employed in this study, 2,4-D appeared to be the most potent as it not only reduced the radial mycelial growth rate with increased concentration like the other herbicides, but resulted in a100% mycelial growth inhibition of all the fungi at 1% v/v.…”
Section: Discussionmentioning
confidence: 91%
“…This can be concluded from results that lignolytic enzymes are tolerant to selected concentrations (55 mg kg -1 ) of Endosulfan. P. ostreatus is considered the most tolerant fungus to many pollutants [34] and the increase in Laccase and MnP activity during the incubation under SMF and SSF conditions due to Endosulfan spiking is in accordance with the earlier observations [34] that observed the higher activity of Laccase in the presence of atrazine than its associated control. This seems unusual because generally the addition of pollutants decreases lignolytic enzyme activities.…”
Section: Effect Of Endosulfan On Activities Of Lignolytic Enzymessupporting
confidence: 88%
“…Laccases (EC 1.10.3.2), lignin peroxidases (LiP; EC 1.11.1.14) and manganese peroxidases (MnP; EC 1.11.1.13) are responsible for the degradation of the most recalcitrant molecule in nature [8]. Thus, the co-metabolic biodegradation of pesticides, PAHs (polycyclic aromatic hydrocarbons), polychlorinated phenols, polymers, dioxins, pesticides, and dyes by ligninases have been subject of intense research [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%